2022
DOI: 10.1111/jep.13780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fast‐and‐frugal clinical decision algorithm (‘pathways’) on clinical outcomes in hospitalised patients with COVID‐19 treated with anticoagulants

Abstract: Rationale, Aims and Objectives Critics have charged that evidence‐based medicine (EBM) overemphasises algorithmic rules over unstructured clinical experience and intuition, but the role of structured decision support systems in improving health outcomes remains uncertain. We aim to assess if delivery of anticoagulant prophylaxis in hospitalised patients with COVID‐19 according to an algorithm based on evidence‐based clinical practice guideline (CPG) improved clinical outcomes compared with administration of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…However, CPs are theory‐free constructs that require further modifications to allow the quantitative analysis of delivery healthcare interventions 27,31 . Indeed, we have previously demonstrated that this is possible by converting CPs into FFT—the latter have a strong theoretical basis to facilitate the calculation of the correct delivery of a given management strategy 28,31,32 . Note that we somewhat simplified the pathway/FFT for high prior PE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CPs are theory‐free constructs that require further modifications to allow the quantitative analysis of delivery healthcare interventions 27,31 . Indeed, we have previously demonstrated that this is possible by converting CPs into FFT—the latter have a strong theoretical basis to facilitate the calculation of the correct delivery of a given management strategy 28,31,32 . Note that we somewhat simplified the pathway/FFT for high prior PE.…”
Section: Methodsmentioning
confidence: 99%
“…27,31 Indeed, we have previously demonstrated that this is possible by converting CPs into FFT-the latter have a strong theoretical basis to facilitate the calculation of the correct delivery of a given management strategy. 28,31,32 Note that we somewhat simplified the pathway/FFT for high prior PE. That is, the ASH considers PE ruled in if CTPA is positive.…”
Section: Decision-theoretical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating pathways into FFT can enable such evaluation. 7,16,26 An FFT decision tree consists of a series of sequential predictors or "cues" that are most relevant to categorising each patient (or a group of patients) into binary outcomes. Every cue throughout the tree has a single exit ("yes" [y] or "no" [n]) except the last cue.…”
Section: A Conceptual Outlinementioning
confidence: 99%
“…The standard FFT deals with classifying outcomes but does not consider the consequences of decisions, which FFTT does. 7,16,26 FFTT stipulates that rational administration of treatment or diagnostic tests occurs when the expected treatment benefits outweigh its expected harms at a given probability of disease or clinical outcome. 7,16,26 The accuracy of FFT and FFTT is defined by their exit structure, which determines the ratio between false negatives and false positives (see Supporting Information: Appendix Figure S1 for details).…”
Section: A Conceptual Outlinementioning
confidence: 99%